EFEKTIVITAS ORGANISASI DALAM PELAKSANAAN PEMBANGUNAN INFRASTRUKTUR DI DESA SOTOL KECAMATAN LANGGAM KABUPATEN PELALAWAN TAHUN 2011-2013 - Silvianis, Reza; ", Sujianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Infrastructure development in reconstructing the village must be able to accommodate the societies’ aspirations, apply the societies’ active role to participate actively in societies for staying together as villagers. Government has authorities to manage the interests of the societies, but the infrastructure activities that have been realized in the Sotol still entrusted to the private sector as doer.The problem that was discussed in this thesis was how the organization effectiveness in building the infrastructure in Sotol, Langgam subdistrict Palalawan. Also, the others factor that obstruct the processes.The method that was used in this research was description qualitative analysis. The collecting data were primer and secondary data. The primer data was gotten from observation and interview some of proper respondents and secondary data was gotten from library study. It also used purposive sampling in determining the sample.The result of this research was the effectiveness in building infrastructure in Sotol was not good enough yet. It could be seen from building realization which was planned just carried out only two kinds. The factors that influence the monitoring forward the low responsible and awareness about infrastructure building, less of builders, and hard to reach the location. So, the suggestion in this thesis is, because of less fund, it is needed to give job division clearly, transpiration between government and other parties which are involved in societies needs. Also, optimizing the planning about infrastructure building. The government may give explanation clearly about infrastructure, so that sub district and district can control the maintenance of the infrastructure.Key Word : Village, Organizations, Infrastructure and Developme